EXPERIMENTAL PROCEDURE FOR SLIP FACTOR DETERMINING AT CONNECTIONS WITH PRELOADED BOLTS (Advances in Civil and Architectural Engineering, 2014)
This article presents the advantages of using preloaded bolts in connections of steel structures. First we discussed the main differences between preloaded bolts and shear bolts. Then we explained the categories of shear connections and the categories of friction surfaces, along with their associated surface preparation and slip factor. To connect theory and codes with experiment, we showed the basic expressions used to calculate the design resistance of preloaded bolts and compared the design resistance of shear bolts. The slip factor was tested according to EN 1090-2:2008, Annex G, for two series of specimens, identical to those used in bridges in the Republic of Albania.